Archaeozoological Complex of the Makaryevskoye Hillfort - Asylgaraeva Gulshat Sh.; Orudzhov Eduard I.; Starkov Andrey S. (Поволжская археология, 2022)
The paper features the results of a study of archaeozoological materials from the excavations of 2018 at the Makaryevskoye hillfort located in the Verkhneuslonsky District of the Republic of Tatarstan. The completed species, age and breed studies have revealed the composition of domestic and wild game fauna, and the role of individual animal species in the life and nutrition of the local population. Their comparison with similar information obtained at the excavations of other sites of the Ananyino and Imenkovo periods has allowed to identify similarities and differences in the herd composition of the population of the Volga and Kama region hillforts. Wild game fauna is represented by bone remains of elk, bear, boar, fox, beaver and hare. According to the herd composition of domestic animals and the content of bone fragments of the hunting and fishing fauna, the Makaryevskoye hillfort is a typical monument of the Early Iron Age and the Early Middle Ages.